The private library of the Infanta María Isabel Francisca de Asís Borbón, “la Chata” - Domingo Malvadi, Arantxa (Revista General de Información y Documentación, 2017)
Little or no research has been made until now on the private library of the Infanta Isabel, “la Chata” (1851-1931), daughter of Queen Isabel II. Starting point of our study is an unpublished inventory of the Infanta’s books acquired during her childhood and adolescence, before her marriage in 1868. The identification of the items and a preliminary approach to their content points to a library intended for the education of a member of the royal family, with books on religion and moral, calligraphy and grammar, literature, modern languages and history, as well as on mathematics, natural sciences and music, with few concessions to simple entertainment. The comparison of the inventory with the school notebooks of the Infanta preserved in the Royal Library (Madrid) allows us to draw a more exact profile of her instruction.